Dual-Scheimpflug-Placido-disc corneal analysis in cats - Ramos, Letícia de Andrade [UNESP] (2022)
Objective: To evaluate the corneal topography and tomography of cats using a dual Scheimpflug and Placido disc device. Animal studied: Sixteen mixed-breed cats (32 eyes). Procedure(s): Cats were sedated using meperidine (4.3 mg/kg/IM) and xylazine (0.5 mg/kg/IM), and evaluated using the software Galilei™. Values assessed included anterior and posterior corneal curvature, total corneal power, and corneal thickness. Results: Ten males and six females aged between 18 and 48 months were evaluated. The simulated keratometry (SimK) was 38.37 ± 0.83D, mean posterior keratometry −4.89 ± 0.34D, and mean total corneal power 38.04 ± 0.94D. The mean central corneal thickness (CCT) was 617.34 ± 53.38 μm with a mean thinnest point of 583.74 ± 60.60 μm. Conclusion: The Galilei™ examination was feasible in cats, enabling a detailed study of the cornea. To the best of our knowledge, this is the first study evaluating the corneal topography and tomography of cats using a device that integrates data from a dual Scheimpflug and Placido disc system.